Tracking Mobile Medical Equipment with iBeacons - Davison, Richard (My University, 2017)
With the complex structure and stressful environment, hospital staff have difficulties locating mobile medical equipment. The equipment is often expensive resulting in costly over procurement to solve localizations and utilization issues. This report describes how a resource location tracking system with iBeacons could be implemented and visualized as an alternative solution. The report also constitutes possible issues and considerations in regards to tracking of mobile medical equipment. Compact mobile medical equipment, such as external pacemakers, usually have a high cost and is more prone to misplace. However, manufacturer regulations, disclaimers and formalities prevent additions of the technical components required to implement the suggested Bluetooth tracking solution presented in this report.
Keywords: Data- och informationsvetenskap; Informations- och kommunikationsteknik; Computer and Information Science; Information & Communication Technology